Agile R&D Units' Organization Beyond Software-Developing and Validating a Multidimensional Scale in an Engineering Context - Meier, Andre; Kock, Alexander (IEEE transactions on engineering management, 2022)
Previous literature addressed organizations' adaptiveness to ever-changing business environments and investigated the concept of agility. However, extant agility research primarily covers the corporate and project levels and is typically located in the information systems and operations management fields. Relatively little quantitative research in innovation management literature exists, and those studies approached the concept solely from an outcome perspective (i.e., increased adaptiveness) instead of elucidating how organizations should organize themselves to be agile (i.e., a capability perspective). This article addresses these shortcomings and adopts a capability perspective since no empirical studies have examined agile R&D units' organization (ARDO). Drawing on dynamic capabilities theory, we develop a measure of ARDO, conceptualizing it as a second-order construct, consisting of six dimensions: a culture of agile values, customer integration, autonomy, an iterative work method, cross-functional capabilities, and flat hierarchies. We validated the measurement by conducting three studies to ensure content, structural, and nomological validity. We applied structural equation modeling on a sample of 175 R&D managers and cross validated our findings on different hierarchical levels via a sample of 454 R&D employees. The results confirm the second-order nature of the ARDO measure and provide evidence of its positive relationship with front-end success. We advance scarce quantitative research on agility's neglected capability perspective and contribute to the innovation management field by facilitating further empirical research on agile R&D units' antecedents and outcomes in the context of physical product development.